Pemetaan Infrastruktur Pengelolaan Sampah Berbasis Masyarakat (PSBM) Menggunakan Sistem Informasi Geografis (SIG) dengan Wilayah Studi di Kabupaten Sleman, Yogyakarta: Indonesia - Satria, Muhammad Rifqi; Putra, Hijrah Purnama; Wacano, Dhandhun; Yuriandala, Yebi (UII, 2026)
The population growth in Sleman Regency has led to an increase in waste generation, necessitating an effective and participatory management system. This study aims to map the distribution of Community-Based Waste Management (CBWM) infrastructure, such as TPS3R, waste banks, and